PENINGKATAN KINERJA GURU MELALUI INOVASI, KOMPENSASI DAN KOMPETENSI GURU PADA SEKOLAH KHUSUS SWASTA DI KABUPATEN TANGERANG - Wulandari, Rosiana; Pujilestari, Yulita; Trihandayani, Estiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher performance is a key factor in improving the quality of education, particularly in private special schools that serve students with diverse characteristics and face more complex educational service demands. Nevertheless, teacher performance in private special schools still encounters various challenges, including limited instructional innovation, suboptimal compensation systems, and variations in teacher competence. This study aims to analyze the relationship between innovation, compensation, and teacher competence and teacher performance in private special schools in Tangerang Regency, both partially and simultaneously. The study employed a quantitative approach using an associative method. The research population consisted of all teachers in private special schools in Tangerang Regency, with a sample of 105 teachers. Data were collected through structured questionnaires and analyzed using multiple regression analysis. The results indicate that innovation, compensation, and teacher competence have a positive and significant effect on teacher performance, both partially and simultaneously. These findings suggest that improving teacher performance in private special schools can be achieved through strengthening a culture of innovation, providing fair and adequate compensation, and continuously developing teacher competence. This study is expected to contribute theoretically to the development of educational management studies and serve as a practical consideration for school administrators and policymakers in formulating strategies to enhance teacher performance in private special schools.